Machinability and tribological investigation of nano-hybrid cryogenicMQL during milling Ti-6Al-4V alloy - Musfirah, Abdul Hadi (Malaysian Tribology Society (MYTRIBOS), 2025)
This paper examines the end milling of Ti-6Al-4V alloy using a nano-hybrid cryogenic-minimum quantity lubricant (MQL) cooling system, focusing on tribology, tool wear, tool life, and surface roughness. Experiments were conducted at cutting speeds of 130 and 150 m/min, feed rates of 0.2 and 0.5 mm/rev, and a constant depth of cut of 0.5 mm using a single insert carbide tool. The nanohybrid cryogenic-MQL system was the primary cooling method, and a four-ball tribometer was used for tribology studies. Tribology experiments showed that incorporating nanoparticles in MQL resulted in a lower coefficient of friction (0.131) compared to MQL without nanoparticles (0.146) at 3500 seconds. The results also highlighted the importance of cooling systems and cutting parameters in optimizing tool wear, tool life, and surface roughness. It was found that a cutting speed of 130 m/min and a feed rate of 0.2 mm/rev significantly improved tool life by approximately 50% and a cutting speed of 130 m/min and a feed rate of 0.2 mm/rev produced better surface roughness compared to other parameters. In conclusion, the nano-hybrid cryogenic-MQL system enhances machinability and meets industry requirements, proving to be a viable, environmentally friendly, and sustainable cooling alternative.